AGING WITH DIGNITY: THE ROLE OF SOCIAL WELFARE PROGRAMS IN ENHANCING ELDERLY QUALITY OF LIFE IN IBADAN, OYO STATE, NIGERIA - Ajibike Fatoye, Helen; Samuel Fatunbi, Boluwatife (African Journal of Social and Behavioural Sciences, 2026)
Nigeria’s rapidly aging population presents a formidable challenge to existing social welfare architecture, particularly within rapidly urbanizing southwestern cities such as Ibadan, Oyo State. This study examined the role of social welfare programs in enhancing the quality of life of elderly persons in Ibadan, with specific attention to health care access, social support structures, and economic security provisions. Using a descriptive survey design, data were collected from 384 elderly respondents aged 60 years and older, selected using a multi-stage stratified random sampling technique. Four validated instruments were used: the WHOQOL-BREF scale, the Social Support Survey (SSS), the Economic Security Questionnaire (ESQ), and the Social Welfare Program Accessibility Scale (SWPAS). Healthcare access significantly predicted quality of life (β = .48, B = 0.62, p < .001), explaining 41% of variance (R² = .41). Social support showed strong positive correlations with psychological well-being (r = .53), social relationships (r = .61), and overall quality of life (r = .59), all p < .001. Economic security was significantly associated with environmental quality of life (r = .58) and total quality of life (r = .54), p < .001. Quality of life differed significantly by welfare participation level, F(2,381) = 18.43, p < .001, with means increasing from low (51.4) to moderate (57.8) to high (65.3), confirming a dose-response effect. These findings hold critical implications for policy reform, social work intervention, and the reimagination of elderly care in Nigeria. The study recommends the expansion of the National Home Care Programme, strengthening of the National Social Investment Programme, and integration of gerontological social work competencies into professional training curricula.